2000
DOI: 10.1034/j.1600-0846.2000.006002087.x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary pH and influence of deodorants

Abstract: BACKGROUND/AIMS: In moist intertriginous regions, such as the armpit, the pH value is physiologically higher than in other skin regions. The regulation of the axillary pH-value was examined in an open study with 48 subjects in three groups with n=16 each. METHODS: In the first 10 days (run-in) the subjects received a standard treatment in the axilla with shaving, cleansing and application of a pH-neutral deodorant. This was followed by a 5 day treatment period with the three test products (pH5 Eucerin(R) Deodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 7 publications
2
15
0
1
Order By: Relevance
“…These parts are prone to infections or high-density colonization by microorganisms. Many deodorants are developed to control armpit microflora and, because of this [64], body odor, by decreasing skin pH to a value around 5.5 [58]. Whether this claimed activity is due to a direct effect of acidic pH on bacteria and body odor is, however, not obvious.…”
Section: Role Of the Skin Ph Ph And Skin Microfloramentioning
confidence: 99%
See 1 more Smart Citation
“…These parts are prone to infections or high-density colonization by microorganisms. Many deodorants are developed to control armpit microflora and, because of this [64], body odor, by decreasing skin pH to a value around 5.5 [58]. Whether this claimed activity is due to a direct effect of acidic pH on bacteria and body odor is, however, not obvious.…”
Section: Role Of the Skin Ph Ph And Skin Microfloramentioning
confidence: 99%
“…data]. Deodorants containing pH-regulatory ingredients and other topical products have been reported to affect the skin surface pH, at least for a few hours [58,59]. However, little is currently known about possible physiologic consequence(s) of such changes.…”
Section: Exogenous Factorsmentioning
confidence: 99%
“…Shaving the hairy armpit vault markedly reduces the body surface enriched in micro-organisms, thus limiting the area releasing the odorous volatile compounds. Decreasing the skin pH has been claimed to improve the efficacy of some deodorants [41,48]. Other variables involved in body odour control are similar to those described for antiperspirants [49].…”
Section: Factors Influencing Efficacymentioning
confidence: 65%
“…In these respects, there is a concentration-dependent antiperspirant efficacy of metal salts up to a plateau value corresponding to a saturation effect. At equal molar concentrations, most aluminium salts exhibit greater antiperspirant efficacy with decreasing pH [41,42].…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Stenzaly-Achtert et al showed that there are pH differences in different body regions and revealed the correlation between a high skin pH and the growth of several microorganisms that produce malodor [8].…”
Section: Introductionmentioning
confidence: 99%